2015
DOI: 10.18632/oncotarget.5797
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib-induced defective autophagy promotes cell death by necroptosis

Abstract: Autophagy is one of the main cytoprotective mechanisms that cancer cells deploy to withstand the cytotoxic stress and survive the lethal damage induced by anti-cancer drugs. However, under specific conditions, autophagy may, directly or indirectly, induce cell death. In our study, treatment of the Atg5-deficient DU145 prostate cancer cells, with the multi-tyrosine kinase inhibitor, sorafenib, induces mitochondrial damage, autophagy and cell death. Molecular inhibition of autophagy by silencing ULK1 and Beclin1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 54 publications
(58 reference statements)
0
43
1
Order By: Relevance
“…2B). By contrast, a recent study reported that sorafenib induces EGFP-LC3 foci formation in DU145 cells (17). The results of the present study indicated that Tet could not induce EGFP-LC3 puncta formation, but it increased the number of autophagosomes in DU145 cells.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…2B). By contrast, a recent study reported that sorafenib induces EGFP-LC3 foci formation in DU145 cells (17). The results of the present study indicated that Tet could not induce EGFP-LC3 puncta formation, but it increased the number of autophagosomes in DU145 cells.…”
Section: Discussioncontrasting
confidence: 99%
“…It may either lead to cell death or maintain cell survival against chemotherapeutic drugs. In DU145 cells, sorafenib blocks the autophagic flux, whereas transiently re-expressing ATG5 in DU145 cells antagonizes sorafenib-induced cell death (17). Therefore, the present authors postulate that the autophagic flux may be relatively inadequate in DU145 cells.…”
Section: Discussionmentioning
confidence: 67%
“…Accumulating studies have supported RIP1 as a key moderator of cell survival signaling, while other reports have suggested a prodeath role of RIP1. 22,24,55 Wang et al 22 have found that RIP1 played a crucial role in survival through catalase-mediated ROS reduction and maintenance of inhibitor of apoptosis proteins, thus enhancing chemoresistance to cisplatin in human lung cancer A549 cells. The activation of necropotosis was verified by the induction of RIP1 and RIP3, which was abrogated by necropotosis inhibitor necrostatin-1.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that TRAIL-induced necroptosis is a signaling pathway distinct from autophagy; however, some studies suggest that necrosome assembly occurs on autophagosomal membranes, e.g., after treatment with obatoclax, an inhibitor of the antiapoptotic protein Bcl-2 (53), or with the multityrosine kinase inhibitor sorafenib (54). An involvement of the autophagic machinery during necroptosis is still controversial, as necroptosis was shown to be independent of autophagy in murine T cells lacking caspase-8 and FADD (55), but murine T cells deficient for caspase-8 and expressing dominant negative FADD undergo necroptosis via the activation of autophagy by RIPK1 (56).…”
Section: Atg5 But Not Atg16l1 or Receptor Internalization Promotes Trmentioning
confidence: 99%